Digital libraries and some intellectual issues | المكتبات الرقمية وبعض القضايا الفكرية - Bo azza | بو عزة, Abdulmajid | عبدالمجيد (King Fahad National Library | مكتبة الملك فهد الوطنية, 2024)
The emergence of digital libraries represents an important turning point in the history of knowledge transmission and access. After the transfer and dissemination of knowledge depended on material containers such as clay tablets, papyrus, leather, and paper, which were initially used to record manuscripts and then to house the printed book in the middle of the fifteenth century, things changed and digital containers began to contribute significantly to making knowledge available, disseminating, and using it on a large scale, especially After the spread of the Internet in the nineties | يمثل ظهور المكتبات الرقمية منعطفًا مهمًّا في تاريخ بث المعرفة والوصول إليها. فبعد أن كان نقل المعرفة وبثها يعتمد علـى أوعيـــــة ماديــــة مثــل الألــواح الطينيــة والبـــردي والجلد والورق الذي استخدم في البداية لتسجيل المخطوطات ثم لإيواء الكتاب المطبوع في منتصف القرن الخامس عشر، تغيرت الأمور فأصبحت الأوعية الرقمية تسهم بشكل كبير في إتاحة المعرفة ونشرها واستخدامها على نطاق واسع، خاصة بعد انتشار شبكة الإنترنت في التسعينيات